PROTECTIVE EFFECT OF PHYLLANTHUS EMBLICA EXTRACT PREVENT CONTRAST-INDUCED ACUTE KIDNEY INJURY IN RATS - SUPRANEE KONGKHAM; ADIS TASANARONG; ARUNPORN ITHARAT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the anti-apoptosis effect of the extract from Phyllanthus emblica (PE) for the prevention of contrast-induced acute kidney injury (CI-AKI). Methods: Male Sprague Dawley rats were given saline (control) or PE extracts (500 mg/kg/day) for 5 days before the induction of CI-AKI. Renal tissues were collected for an evaluation of gene expression and immunohistochemistry (IHC). To indicate anti-apoptotic effect, the expression levels of Bax, Bcl-2, and caspase in kidney were also determined, using real-time polymerase chain reaction (RT-PCR) and Western blot analysis. Results: In the CI-AKI group, RT-PCR and Western blot analysis revealed that the expression levels of Bax and cleaved-caspase-3 were upregulated in the CI-AKI group, whereas the expression of Bcl-2 was downregulated. However, the pre-treatment with PE increased Bcl-2 expression. Moreover, decreased cleaved-caspases-3 activity was also detected using IHC. Conclusion: These findings suggested that pretreatment with PE extract provided the anti-apoptotic effect against CI-AKI in the rat model.